Edukasi Mitigasi Bencana Gempa Berdasarkan Persyaratan Pokok Rumah yang Lebih Aman di Kampung Badran, Bumijo, Yogyakarta - Suharno, Yohanes Eudes; Ayuningtyas, Nurina Vidya; Dwi Wismantoro, Bayu (Jurnal Ilmiah Padma Sri Kreshna, 2024)
One of the spaces needed for urban communities, one of which is the public area (public space). The condition of open space / open space RW 04 Kelurahan Bener Yogyakarta City is quite interesting to note. Some areas of open space are used by the community not according to their main function. It is hoped that the solution of the design to problems that exist in the field can provide benefits to the surrounding community, such as making areas that look unorganized become designed and do not create a slum impression. The use of linear open space with a good design in dense areas can give an aesthetic impression to an area and provide many benefits, especially in social terms, cleanliness can also be reflected because in general, slum areas often occur / form slums. In addition, the design proposal with the concept of the character approach that is owned by RW 04, Kelurahan Bener is a KB village. by applying it as a social, economic, and ecological function. Point one is focused on bringing out the village character, the second point is character and improves the function of the information board and the third point is improving the function of the gathering place.Keywords: Open Space, Linear Open space, KB Village, Ecology